2011
DOI: 10.4100/jhse.2011.64.04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined electrostimulation and plyometric training on vertical jump and speed tests

Abstract: Benito-Martínez E, Lara-Sánchez AJ, Berdejo-del-Fresno D, Martínez-López EJ. Effects of combined electrostimulation and plyometric training on vertical jump and speed tests. J. Hum. Sport Exerc. Vol. 6, No. 4, pp. 603-615, 2011. The aim of this study was to determine the performance evolution of a group of athletes after 8 weeks of training that combined electrostimulation (NM ES) and plyometrics (PT). 78 medium level sprinter athletes participated, 40 women and 38 men (age, 15.9±1.4 years old, body mass inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
9
1
2
Order By: Relevance
“…However, the decrease was of only 4.83% in the EXP group and the ES was moderate. Our findings appear to contradict those obtained by Benito-Martínez et al [20] and Benito-Martínez et al [21], who observed a higher decrease in 30 m sprint-time when electrostimulation was superimposed with PT. These differences may be explained by two main reasons: on the one hand, our PT + WBES combined program was actually performed only once a week; on the other hand, the PT carried out by those authors was actually of lower intensity than ours, with only 48 contacts per session.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the decrease was of only 4.83% in the EXP group and the ES was moderate. Our findings appear to contradict those obtained by Benito-Martínez et al [20] and Benito-Martínez et al [21], who observed a higher decrease in 30 m sprint-time when electrostimulation was superimposed with PT. These differences may be explained by two main reasons: on the one hand, our PT + WBES combined program was actually performed only once a week; on the other hand, the PT carried out by those authors was actually of lower intensity than ours, with only 48 contacts per session.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the functional transfer of these gains into sports movements is more relevant [16] and, in order to achieve this functional transfer and to develop higher force and power, electrostimulation has to be combined or superimposed with sport-specific exercises [17,18]. Its simultaneous combination with PT has proven to be more effective for the improvement in vertical jump ability [19] and 30 m sprint-time [20,21] than PT alone.…”
Section: Introductionmentioning
confidence: 99%
“…In volleyball, high jumping ability greatly affects a player’s ability and, therefore, diverse methods for exerting explosive power in the lower limbs have been introduced. Among them, plyometric training enables the exertion of explosive power using the extension reflex by the action of actin-myosin within the muscles 4 ) . Therefore, it is widely applied as a training method to develop greater power, through the improvement of muscle strength and speed, for to producing superior exercise performance in ordinary people, as well as in athletes whose sports rely heavily on jumping, such as basketball, and track and field, as well as volleyball 5 , 6 , 7 , 8 ) .…”
Section: Introductionmentioning
confidence: 99%
“…-150 Hz podem conduzir a melhora da força explosiva (Benito-Martínez et al, 2013;Martínez-López et al, 2012). Entretanto, alguns autores demonstraram que o aumento da frequência de estimulação (≥ 60 Hz) está diretamente relacionado com um aumento da fadiga muscular (Bickel et al, 2003;Gregory et al, 2005).…”
Section: Estimulação Elétrica Neuromuscularunclassified
“…Nesse sentido, alguns estudos vêm utilizando a aplicação da estimulação elétrica neuromuscular (EENM) para a melhora das capacidades de força, potência de salto e velocidade, contribuindo para o aumento do desempenho de atletas de modalidades esportivas distintas, tais como: Basquete, com um aumento de 14% no squat jump (SJ), aumento de força isométrica, isocinética concêntrica e excêntrica, após 8 semanas de treinamento (Maffiuletti et al, 2000); Voleibol, com um aumento de 6,5% e 5,4% no SJ e salto contra movimento (SCM), respectivamente, após 3 semanas de treinamento (Malatesta et al, 2003); Futebol, com um incremento de 6,7% e 2,27% do SJ e SCM, respectivamente, após 5 semanas de treinamento (Billot et al, 2010); Rugby, com aumento de força isocinética concêntrica e excêntrica, incremento de 15% na força de agachamento e melhoria de 10% para o SJ, após 12 semanas de treinamento (Babault et al, 2007); Tênis, com o tempo de sprint de 10m reduzido em 3,3% e aumento de 6,4% da altura do SCM, após 3 semanas de treinamento (Maffiuletti et al, 2009); e Atletismo, com aumento de 11,2% SJ, com o tempo do sprint de 30m, reduzido em 6,78% e aumento de 5,21% para o salto triplo, após 8 meses treinamento (Benito-Martínez et al, 2013).…”
Section: Introductionunclassified